Potencial quimioterápico da berberina em linhagens celulares de glioblastoma multiforme comparado ao tratamento padrão - Bortoluzzi, Luisa Donato (2025)
In Brazil, it is estimated that more than eleven thousand cases of primary central nervous system (CNS) tumors occur each year, with approximately 80% of malignant CNS tumors being gliomas. Glioblastoma multiforme (GBM), a type of glioma, is the most common and lethal malignant brain tumor, leading to a poor prognosis for patients. Due to the low response to conventional treatment with temozolomide (TMZ), the search for new potential drug therapies becomes essential. In this context, berberine (BBR), found in plants of the Berberidaceae family, has emerged as an alternative for GBM treatment due to its antitumor activity and ability to cross the bloodbrain barrier (BBB). However, there is no evaluation of the chronic activity of BBR compared to TMZ, nor whether a synergistic effect exists between the drugs. Therefore, this study evaluated the in vitro chemotherapeutic potential of BBR, both acutely and chronically, in comparison and combination with the drug used in the standard GBM treatment in cell lines sensitive and resistant to this therapy. The results demonstrated that BBR exerts a cytotoxic effect in a dose- and time-dependent manner, being more effective at 50 µM after 72 hours and 7 days. Its combination with TMZ enhanced cytotoxicity, suggesting an additive effect. Additionally, BBR inhibited colony formation, particularly in the A172 cell line, and reduced cell migration, while TMZ alone did not impact the mobility of U138 cells. These findings highlight the potential of BBR as an antitumor agent, especially in combination with TMZ, and emphasize the need for further studies to elucidate its molecular mechanisms and in vivo efficacy.